Mapping Inner and Outer Theater Histories. Mark Pizzato, “Mapping Global Theatre Histories” (London:Palgrave Macmillan, 2019) - CRĂIUŢ, Rareş - Augustin (Studia Universitatis Babeș-Bolyai Dramatica, 2019)
When I was in school the translation of Vitto Pandolfi’s 1964 Storia universale del teatro drammatico was compulsory reading material. The bibliography of theatre history is quite abundant by now, with books such as History of the Theatre by Oscar Brockett and Franklin Hildy, republished from the original 1968, to now at its ninth edition, or the beautifull and very expensive, six volume A Cultural History of Theatre by Christopher Balme and Tracy Davis published in 2017.